Primary Total Knee Arthroplasty Application for Osteoarthritis Developed 17 Years After Curretage–Cementation of Distal Femur Low-Grade Chondrosarcoma - Celayir, Arın; Karaismailoğlu, Bedri; Hız, Veli Muzaffer Murat; Karaismailoğlu, Turgut Nedim (Cerrahpaşa Medical Journal, 2024)
Chondrosarcoma is the second most common primary malignant tumor of bone after osteosarcoma. Prognosis correlates with histological grade. Primary treatment is surgery and neoadjuvant therapies do not play an important role in the treatment algorithm. Surgical options include intralesional curettage and cementation with polymethylmethacrylate, and local resection, reconstruction with tumor resection prostheses. In some patients, degenerative changes in the adjacent joint surface may be seen in the post-treatment follow-up and reconstructive procedures may be needed in the future. Curettage and cementation may increase the risk of osteoarthritis when the procedure is done close to the joint surface. Our case includes knee reconstruction performed 17 years later in a patient who was treated with curettage and cementation for low-grade chondrosarcoma in distal femur. In this case, the cement extending from the femoral diaphysis to the distal end of femur interfered with the placement of alignment guide. However, standard primary knee replacement could be performed without the need for stem or augmentation. Significant clinical improvement was achieved in the follow up. In conclusion, total knee replacement is an effective method for knee osteoarthritis after curettage cementation and low-grade chondrosarcoma, despite some technical difficulties. Cite this article as: Celayir A, Karaismailoglu B, Hız VMM, Karaismailoğlu TN. Primary total knee arthroplasty application for osteoarthritis developed 17 years after curretage–cementation of distal femur low-grade chondrosarcoma. Cerrahpaşa Med J. 2024;48(1):108-110.